The Potential of Cyanobacterial Compounds as Antibiotics - Wright, Mitchell Henry (Pharmacognosy Communications)
cyanobacterial chemistry and the compounds that have antibacterial activity.1 This paper addresses a significant gap in current antimicrobial research by shedding light on the relatively underexplored potential of cyanobacterial compounds as sources of novel antibiotics. In a time when the rise of drug-resistant pathogens presents a significant global health challenge,2 this paper highlights the importance of diversifying the sources of antimicrobial agents, offering fresh perspectives and potential solutions. The authors emphasize the need for further investigation, and encourage continued exploration and highlight priority areas in this promising area of study.